2021
DOI: 10.1016/j.xkme.2020.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Kidney Disease, Endothelial Damage, and Podocyte-Endothelial Crosstalk

Abstract: Diabetes-related complications are a significant source of morbidity and mortality worldwide. Diabetic kidney disease is a frequent microvascular complication and a primary cause of kidney failure in patients with diabetes. The glomerular filtration barrier is composed of 3 layers: the endothelium, glomerular basement membrane, and podocytes. Podocytes and the endothelium communicate through molecular crosstalk to maintain filtration at the glomerular filtration barrier. Chronic hyperglycemia affects all 3 lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 123 publications
0
37
0
5
Order By: Relevance
“…Although animal models are widely used to study human kidney biology and for preclinical drug development, such models often yield results that are not directly applicable to humans due to species-specific differences in biochemical, physiological, developmental, and anatomical characteristics. Furthermore, normal adult or embryonic human tissues are usually unavailable in sufficient amounts for research, and many mouse models [ 8 , 9 , 10 ] do not reliably reproduce human phenotypes or biological responses. As a result, it was found that 89.5 % of preclinical drugs that passed animal testing failed during in-human trials [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although animal models are widely used to study human kidney biology and for preclinical drug development, such models often yield results that are not directly applicable to humans due to species-specific differences in biochemical, physiological, developmental, and anatomical characteristics. Furthermore, normal adult or embryonic human tissues are usually unavailable in sufficient amounts for research, and many mouse models [ 8 , 9 , 10 ] do not reliably reproduce human phenotypes or biological responses. As a result, it was found that 89.5 % of preclinical drugs that passed animal testing failed during in-human trials [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The present observation is a continuation of our previous research, where we showed that the coexistence of AITD in patients with DM1 is associated with a significantly lower risk of developing nonproliferative diabetic retinopathy (NPDR) [ 13 ]. AITD and DKD are associated with endothelial dysfunction [ 14 , 15 ], yet the coexistence of AITD and DKD has not yet been assessed. The aim of the study is to assess the relationship between AITD and the occurrence of DKD in a group of patients with DM1.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, multiple molecular triggers and signalling pathways of glomerular capillary dysfunction contributing to kidney failure have been determined [ 1 , 2 , 3 ]. Yet, despite the significant advances in clinical and experimental research in diabetes and its complications, the diagnosis and effective treatment of DKD remains challenging [ 4 , 5 , 6 , 7 , 8 ]. Noteworthy, due to the metabolic memory in diabetes (an emergent and rapidly evolving epigenetic-related mechanistic concept) and in spite of the therapeutic control of hyperglycaemia, diabetes pathological long-lasting effects persist and continue to promote systemic cellular detrimental effects [ 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic kidney disease (DKD), the major microvascular complication of both type I and type II diabetes, is a complex multifactorial renal disorder having a detrimental impact on the patient’s quality of life and life-span expectation [ 1 , 2 , 3 ]. Dysfunction of glomerular endothelial cells and podocytes, thickening of the glomerular basement membrane, mesangial cells hypertrophy and proliferation, progressive accumulation of mesangial extracellular matrix (ECM) components, podocyte damage, and disruption of glomerular endothelium fenestrations are the main structural alterations ultimately leading to glomerulosclerosis; a pathological condition that is further responsible for increased intraglomerular capillary pressure, hyperfiltration, and eventually kidney failure [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%